Cytotoxic effects of different detergent containing children's toothpastes on human gingival epithelial cells - AKKOÇ, TUNÇ (My University, 2022)
Background This study aimed to evaluate possible cytotoxic effects to gingival epithelial cells exposed to children toothpastes containing different detergent. Methods Tissues required for the isolation of human gingival epithelial cells were obtained by biopsy during the extraction of the impacted third molar tooth. Toothpaste solutions of different concentrations were prepared from five different children\"s toothpastes with different detergent contents. Isolated gingival epithelial cells were stimulated with experimental groups consisting of toothpaste solutions (Colgate, Sensodyne, Splat, Nenedent, Perlodent) at different concentrations and a control group consisting of complete Dulbecco\"s modified eagle medium. After the experiments, cell viability was evaluated using flow cytometry. 2 Way ANOVA was used to see the interaction effect of the main effects of toothpaste solution and concentration factors. Pairwise comparisons were made by Tukey post hoc tests. In the study, the significance level was taken as 0.05. Results As a result of the analysis, it was seen that the toothpaste solution and concentration factors and the interactions of these 2 factors were effective on the viable, early apoptotic, late apoptotic and necrotic cell rates. The statistically highest live cell ratios were detected in Splat\"s toothpaste solutions (90.14% at 0.4% concentration) after the control group (90.82%) and the group with the lowest viability values was determined in Colgate group (75.74% at 0.4% concentration) (p < 0.05). Conclusions According to the results of the study, it was observed that toothpastes containing SLS affected the viability of cells more negatively than toothpastes with other detergent contents.
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Orthodontics; Oral Surgery; Dentistry (miscellaneous); Dental Hygiene; Periodontics; Dental Assisting; General Dentistry; Toothpaste; Stem cell; Annexin V; Detergent; SLS; SODIUM LAURYL SULFATE; ORAL-MUCOSA; PLAQUE; DENTIFRICES; FIBROBLASTS; TOXICITY; HEALTH; MUTANS; Toothpaste; Stem cell; Annexin V; Detergent; SLS